Early psychosocial deprivation alters the refinement of neural dynamics across adolescence - Marta Andujar; Lucrezia Liuzzi; Daniel S. Pine; Charles A. Nelson; Charles H. Zeanah; Nathan A. Fox; Bruno B. Averbeck (Proceedings of the National Academy of Sciences, 2026)
Adolescence is a crucial period for the refinement of neural circuits and cognitive skills. During this time, executive functions mature alongside pronounced structural changes in the brain, including reductions in synapse density. Computational models suggest that synaptic pruning enhances performance by stabilizing neural dynamics—deepening attractor basins and accelerating return to baseline after perturbation. Here, we tested these predictions using EEG data from the Bucharest Early Intervention Project, a randomized controlled trial of foster care as an alternative to institutionalized care. Trial-by-trial EEG residuals during a Flanker task were modeled as a linear dynamical system, and changes in eigenvalue magnitude were tracked across adolescence. Across all groups, eigenvalues decreased with age, consistent with maturation of recurrent computations. However, children with histories of institutional care exhibited consistently higher eigenvalues, suggesting delayed or disrupted refinement of the neural dynamics. Importantly, higher eigenvalues were associated with poorer behavioral performance on the task, linking altered neural dynamics to altered executive functions. These findings demonstrate that early deprivation leaves a lasting imprint on the developmental trajectory of neural dynamics, affecting the maturation of brain systems underlying cognitive control.